Smartplug Home Automation System (SHAS) Using Internet Of Things (IoT) - Wan Muhammad Adam, Azmi (2023)
In an era of technology that is growing rapidly in line with the current of modernization, the use of the "Internet of Things" (IoT) has become one of the critical aspects in ensuring that daily affairs become easier. Therefore, an approach should be taken in applying the use of IoT in daily affairs. Smartplug Home Automation System is one approach in applying home automation by allowing users to control home electronic equipment just by using a smart device. The latest technology, especially the Internet of Things (IoT), can be applied as one of the approaches in ensuring that users can also use advanced technology to facilitate daily affairs. This proposed project uses IoT to control electronic hardware connected to Smartplug Home Automation in real time and can be placed in the house or any location that has a pluggable power source. In this project, this system consists of 3 main components namely, Arduino ESP8266, 2 Channel AC Relay and Extension Plug. 2 Channel AC Relay will control the high voltage current connected directly from the Extension Plug. Data is sent via a Wi-Fi module installed with an Arduino ESP8266 board. The data is sent to a database to process the status of the connected electronic hardware and allow the user to control the switch simply by using a smartphone. The goal of this proposed system is to make it easier for users to control electronic equipment in the home without having to physically close the switch. Iterative and Incremental Model methodology is used as a guide to complete the proposed system from the initial planning phase to the system deployment phase. In the end, the objectives of the proposed system are fulfilled and the functionality of the system should be able to control electronic hardware using a smart phone in real time and can be accessed from any location that has an internet network.